#TITLE_ALTERNATIVE# - BRIAN (NIM : 10104059); Pembimbing Tugas Akhir : Dr. Janson Naiborhu, DANIEL
This final project discuss nonlinear trajectory tracking control problem for a nonholonomic system such as a mobile robot with state constraints. Trajectory tracking is an important behaviour for mobile robots. Design method for a system of nonholonomic motion will be studied through linearization techniques. Stability, controllability and observability issues for a nonlinear system are also studied. The main focus in this final project is the study of trajectory tracking control and design of feedback control law for a mobile robot, which is a system of nonholonomic. A nonlinear tracking controller is then achieved by using the dynamic feedback linearization technique. In addition, the controller is obtained by exploiting simultaneously to solve the tracking and regulation problem of mobile robots with state constraints.